From submission to rebellion : the provinces versus the Center in Russia /: the provinces versus the Center in Russia. (2018) - Shlapentokh, Vladimir; Levita, R (Roman); Loĭberg, M. I︠A︡ (Mikhail I︠A︡kovlevich)
No abstract available